Local policies in the fight against the Covid-19 pandemic - Hamza Çelikyay, Hicran (Central European Public Administration Review, 2022)
Purpose and methodology: This study examines how the COVID-19 pandemic is included in municipal councils’ decisions and investigates the local policies developed through these decisions. Ankara and Rome Municipalities were selected as study samples. Turkey and Italy are both unitary states and their local government structures are similar because their local government systems are part of the Franco group, as defined by Hesse and Sharpe. Both cities have gained the status of metropolitan cities under the legal regulations adopted in recent years. For this reason, Ankara and Rome present similarities in terms of both the areas they serve and the responsibilities of being the capital. The decisions of their municipal councils were reviewed from March to December 2020. The decisions were analysed within the framework of the relevant commissions and application areas, and the local policies implemented in the fight against COVID-19 were put forward. Findings: According to the analyses, the Ankara Metropolitan Municipal Council intensified its decisions on economic support, social assistance, cleaning, public health, and local diplomacy, while the Rome Metropolitan Municipality’s policies focused on security, education, economic support, social assistance, cleaning, and transportation services. As a result, both municipalities brought their COVID-19 proposals to the agenda of the council. Municipal assemblies played a vital role in helping their countries fight the pandemic as administrative units that provide the legal basis for implementing local policies. Strengthening local assemblies and expanding their mandate and responsibility in times of crisis could also support the success of central government policies. The findings reveal that fast and effective solutions delivered by local governments through local policies successfully curbed the pandemic that had spread around the world. Practical Implications: The policies implemented by local governments were impressive and complementary to central government policies, providing a valuable guideline for policymakers.
Keywords: Ankara; COVID-19; local government; local policies; lokalne politike; odločitve mestnega sveta; Rim; Rome